Hysteresis, endogenous growth, and monetary policy - Sebastián Amador (University of California, Department of Economics, 2022)
I provide evidence of substantial hysteresis (i.e., a situation in which temporary shocks have longrun effects) from monetary shocks on two sources of endogenous growth; human capital and technological adoption. This contribution is the first to test for the presence of this phenomenon in direct measures of the supply-side potential of economies, instead of indirect measures, e.g., TFP. To estimate the effects of exogenous monetary policy shocks, I improve on the the trilemma identification by incorporating a mean-unbiased instrumental variable estimator. Results show substantial hysteresis in both human capital and technological adoption. Importantly, these are found to be asymmetric, as only contractionary shocks result in long lasting responses. I evaluate the aggregate importance of monetary hysteresis with a growth accounting exercise. Across the 17 countries in sample, the accumulated average cost of monetary hysteresis ranges between 1.2 and 9.6% of TFP, for human capital and the adoption of electricity, respectively.
Keywords: E01; E30; E32; E44; E47; E51; F33; F42; F44; 330; hysteresis; money non-neutrality; endogenous growth